Urbanization and Growth: Why Did the Splendor of the Italian Cities in the Sixteenth Century not Lead to Transition? - Bruno Chiarini; Elisabetta Marzano (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this paper we investigate the relation between population, wages and urban population in the Italian economy. During the period examined, 1320-1870, the prevailing conditions were those of a poor, mainly agricultural economy with limited human capital and rudimentary technology. However, these centuries witnessed the considerable growth of urban centers, a significant demographic phenomenon with major economic consequences. Against this background we set up a theoretical scheme to explain why urbanization did not drive the economy to sustained growth. Our main contribution, validated by an estimated VAR model, suggests that in an early stage of development, migration to cities may have negative consequences for rural marginal productivity. The analysis provides a picture of a trapped economy where urbanization was unable to trigger a persistent process of development without the support of a substantial increase in population.
Keywords: N33; N53; N93; J11; C32; 330; urbanization; Malthusian dynamics; pre-industrial labor productivity; population trend; demographic changes; agricultural wages